Implementation of a computer database testing and analysis program. - Rouse DP (CIN: Computers, Informatics, Nursing)
The author is the coordinator of a computer software database testing and analysis program implemented in an associate degree nursing program. Computer software database programs help support the testing development and analysis process. Critical thinking is measurable and promoted with their use. The reader of this article will learn what is involved in procuring and implementing a computer database testing and analysis program in an academic nursing program. The use of the computerized database for testing and analysis will be approached as a method to promote and evaluate the nursing student's critical thinking skills and to prepare the nursing student for the National Council Licensure Examination.